SIMULATION OF RING CONNECTION MODIFICATION ON FLARE STACK STRUCTURE - Budi Satiawan; Basit Al Hanif; Tanjung Rahayu Raswitaningrum (International Journal of Civil Engineering and Infrastructure, 2022)
The flare stack serves to protect process equipment facilities against unexpected overpressure. This study aims to follow up on previous research that recommends improvements to the flare stack structure based on corrosion findings that occur in the area of the riser stack around the ring connection for the guy wire. By replacing rusty material, it is also necessary to consider modifications to prevent the risk of re-corrosion. Based on current design observations in the connection ring area for guy wire, side cutting is required which can result in water being trapped. This research aims to find out whether by modifying the connection ring for guy wire, this flare structure still has structural reliability when receiving critical outer loads or not. Based on the results of the study, it shows that modifying the geometry of the connection ring guy wire still provides reliable structural performance when receiving critical outer loads. The maximum stress that occurs in the area around the pad eye is 71.2 Mpa with a maximum stress ratio of 0.434 it shows that the value is still quite far from the maximum allowable voltage ratio of 1.0. So it can be concluded by modifying the connection ring for guy wire to prevent the risk of corrosion can be done without causing a decrease in the performance of the structure in withstanding critical outer loads.